Obstacles to the acquisition of research skills by Jordanian undergraduates from the perspective of academic staff and students - Abdel Rahman Mitib Altakhaineh; Israa Qallab; Arwa Sabbah Sabbah; Amal Ghassan Abu Dlu (Social Sciences and Humanities Open, 2025)
The acquisition of research skills among undergraduate students in Jordan has been limited by various institutional and personal factors. This issue has become increasingly apparent as Jordanian educational institutions work to improve the quality of their outputs, as recommended in King Abdullah II's vision and the National Strategy for Human Resource Development. Undergraduate students in Jordan face obstacles in gaining experience in scientific research, which has led to national calls for further investigation of the factors that hinder the development of research skills at this level. This study explores these obstacles from the perspectives of both academic staff and students. Semi-structured interviews were conducted with thirty academic staff members and sixty undergraduate students to gather insights into theirs experiences and opinions. The results indicate that several factors hinder the acquisition of research skills, including the educational environment, lack of mentorship, limited funding and resources, bureaucracy, low motivation English language difficulties, and technological illiteracy. Based on these findings, the study emphasizes the need for policies that promote a research culture that extend it to school and university education. The study, thus, concludes by suggesting the importance of enhanced coordination between the Jordanian Ministry of Higher Education and Scientific Research and the Ministry of Education to develop a strategic plan that fosters and sustains research-based education in the country.